Pendugaan Keragaman Genetik dan Korelasi Antara Komponen Hasil Kacang Hijau Berumur Genjah - Ratri Tri Hapsari (Buletin Plasma Nutfah, 2014)
Estimation of Genetic Variability and Correlation Among Early Maturity Mungbean Yield Components. Ratri T. Hapsari. Early maturity mungbean [Vigna radiata (L.) Wilczek] is very important to avoid drought stress, pest and disease attack as well as increase the index planting. The aims of this research was to estimate genetic variability and correlation. The genetic study included heritability, coefficient of genetic variability, genetic advance and correlation among yield components so that it can be used as selection criteria for early maturity mungbean. A total of 145 accessions of mungbean were tested at Muneng farm station in March-June 2010 using a randomized block design, with two replicates. Each accession was planted at 0.8 m x 4 m with spacing 40 cm x 10 cm, with two plants/hole. Fertilization was done by adding 50 kg urea, 75 kg SP36, and 75 kg KCl/ha, at the time of planting. The results showed that mungbean accesions had significant differences in all characters tested. The genetic variance value of all characters was broad with high broadsense heritability estimates, except for number of pods/ cluster and seed number/pod. Genetic advance of all characters were high, except for seed number/pod. The phenotypic correlation between 1000 seeds weight and pod length with seed yield were positive significant while plant height, flowering days, days to maturity, and number of pods per plant had negative significant correlation with its yield. Therefore, plant height, days to maturity, pod lenght, 1000 seeds weight and seed yield could be used as selection criteria based on estimating value of genetic variability, correlation with yield and economic value. There were five genotype which have index value above 20, i.e MLGV 0353, MLGV 0362, MLGV 0354, MLGV 0358, and MLGV 0351. AbstrakKacang hijau [Vigna radiata (L.) Wilczek] berumur genjah berperan penting untuk menghindari cekaman kekeringan, serangan hama penyakit, dan meningkatkan indeks pertanaman. Penelitian ini bertujuan untuk mengetahui nilai duga parameter genetik dan korelasi antar komponen hasil sehingga dapat digunakan sebagai kriteria seleksi kacang hijau berumur genjah. Sebanyak 145 genotipe kacang hijau diuji di KP Muneng pada bulan Maret sampai dengan Juni 2010 menggunakan Rancangan Acak Kelompok dengan dua ulangan. Setiap aksesi ditanam pada plot 0,8 m x 4 m dengan jarak tanam 40 cm x 10 cm, dua tanaman/lubang. Pemupukan dilakukan dengan 50 kg urea, 75 kg SP36, dan 75 kg KCl per hektar pada saat tanam. Parameter yang diamati adalah tinggi tanaman, umur 50% berbunga, umur 80% masak, jumlah polong/tangkai, jumlah polong/tanaman, panjang polong, jumlah biji/polong, bobot 1.000 biji, dan bobot biji/plot. Hasil penelitian menunjukkan bahwa genotipe yang diuji memiliki keragaman semua sifat yang diamati. Keragaman genetik dan fenotipik tergolong luas. Heritabilitas arti luas tergolong tinggi, kecuali jumlah polong/tangkai dan jumlah biji/polong tergolong sedang. Kemajuan genetik seluruh karakter tinggi, kecuali jumlah biji/polong. Korelasi antara bobot 1.000 biji dan panjang polong bernilai positif nyata dengan bobot biji/plot, sedangkan tinggi tanaman, umur berbunga, umur masak, dan jumlah polong per tanaman berkorelasi negatif nyata. Berdasarkan nilai duga parameter genetik, korelasi antarhasil, dan nilai ekonomisnya, maka tinggi tanaman, umur masak, panjang polong, bobot 1.000 biji dan bobot biji per plot dapat dijadikan kriteria seleksi indeks. Terdapat lima genotipe memiliki nilai indeks lebih dari 20, yaitu MLGV 0353, MLGV 0362, MLGV 0354, MLGV 0358, dan MLGV 0351.